Chronic occupational mold exposure drives expansion of aspergillus-reactive type 1 and type 2 t-helper cell responses - Lauruschkat, Chris D.; Etter, Sonja; Schnack, Elisabeth; Ebel, Frank; Schaeuble, Sascha; Page, Lukas; Rumens, Dana; Dragan, Mariola; Schlegel, Nicolas; Panagiotou, Gianni; Kniemeyer, Olaf; Brakhage, Axel A.; et al. (Journal of Fungi, 2021)
Occupational mold exposure can lead to Aspergillus-associated allergic diseases including asthma and hypersensitivity pneumonitis. Elevated IL-17 levels or disbalanced T-helper (Th) cell expansion were previously linked to Aspergillus-associated allergic diseases, whereas alterations to the Th cell repertoire in healthy occupationally exposed subjects are scarcely studied. Therefore, we employed functional immunoassays to compare Th cell responses to A. fumigatus antigens in organic farmers, a cohort frequently exposed to environmental molds, and non-occupationally exposed controls. Organic farmers harbored significantly higher A. fumigatus-specific Th-cell frequencies than controls, with comparable expansion of Th1- and Th2-cell frequencies but only slightly elevated Th17-cell frequencies. Accordingly, Aspergillus antigen-induced Th1 and Th2 cytokine levels were strongly elevated, whereas induction of IL-17A was minimal. Additionally, increased levels of some innate immune cell-derived cytokines were found in samples from organic farmers. Antigen-induced cytokine release combined with Aspergillus-specific Th-cell frequencies resulted in high classification accuracy between organic farmers and controls. Aspf22, CatB, and CipC elicited the strongest differences in Th1 and Th2 responses between the two cohorts, suggesting these antigens as potential candidates for future bio-effect monitoring approaches. Overall, we found that occupationally exposed agricultural workers display a largely balanced co-expansion of Th1 and Th2 immunity with only minor changes in Th17 responses.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adaptive immunity; Aspergillus; Biomarker; Cytokines; Hypersensitivity; Immunoassay; Inflammation; Mold exposure